2018
DOI: 10.1177/0269094218791508
|View full text |Cite
|
Sign up to set email alerts
|

Supporting rural Small and Medium-sized Enterprises to take up broadband-enabled technology: What works?

Abstract: The last 15 years have seen major changes in the availability and usage of broadband in the UK. Despite these improvements, rural areas continue to lag behind urban areas for broadband connection speeds – a divide that is exacerbated by lower rates of broadband adoption among rural Small and Medium-sized Enterprises (SMEs). This paper examines the experiences of SMEs that have participated in a publicly funded programme designed to stimulate demand for broadband in the rural region of Lincolnshire, UK. Drawing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 27 publications
(42 reference statements)
0
32
0
2
Order By: Relevance
“…Other researchers emphasise that demand-side policies may go beyond demand stimulation by assisting businesses in the use of broadband and associated technologies ( Gillett et al, 2004 ; OECD, 2008 ). This points to the potential for broadband demand-side policies to work alongside supply-side policy measures in an interactive manner, strengthening the use of broadband infrastructure, and addressing low uptake and use in particular groups such as small businesses ( Price et al, 2018 ). It may also suggest new opportunities for public and private actors to collaborate in the delivery of supply- and demand-side policies ( Gómez-Barroso & Feijóo, 2010 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Other researchers emphasise that demand-side policies may go beyond demand stimulation by assisting businesses in the use of broadband and associated technologies ( Gillett et al, 2004 ; OECD, 2008 ). This points to the potential for broadband demand-side policies to work alongside supply-side policy measures in an interactive manner, strengthening the use of broadband infrastructure, and addressing low uptake and use in particular groups such as small businesses ( Price et al, 2018 ). It may also suggest new opportunities for public and private actors to collaborate in the delivery of supply- and demand-side policies ( Gómez-Barroso & Feijóo, 2010 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…SMEs have been identified as an important target group for demand-side policies, with Spurge and Roberts (2005 : 522) arguing that while ‘SMEs have been equipped with the tools [they] are not equipped with skills to use them effectively’. Indeed, studies of SME adoption of digital technologies have shown that while such firms can often lag in their rates of access ( Price et al, 2018 ), active usage can benefit their productivity ( Haller & Lyons, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This has seen extensive efforts, over time, to ensure regions and communities are 'not left behind' in the emerging global and digital economy (Gillespie and Williams, 1988;Gillespie et al, 2001). Such research has increasingly focused on the deployment of broadband infrastructure, but also its use (Grimes, 2003;Price et al, 2018).…”
Section: Broadband Regional Development and Public Policy In The Lasmentioning
confidence: 99%